A hospedagem em Pirenópolis e Goiânia: espaços de preservação e divulgação do patrimônio cultural de Goiás (1989-2006) - Denicolo, Naiara (2006)
This study is aimed at analyzing, in a comparative perspective, the hosting in a tourist city Pirenópolis and in the capital city of Goiás Goiânia, trying to contextualize the authenticity or the simulacrum of these spaces. The methodological procedures employed for such analysis were bibliographical research and field research, with interviews with the owners of different enterprises, which were three inns in Pirenópolis and a hotel in Goiânia. We proceeded to the analysis of the history of Goiás s culture formation, with the evolution of the various types of hotels, and we also attempted to understand the motivational factors, such as leisure or business, that attract tourists to different spaces spaces that are authentic and, therefore, guardians of an identity, or spaces that simulate some sort of cultural rescue. Such spaces represent either cordiality and hospitality or standardized places that follow international laws or suggest a simulacrum. In this last case, the cultural legacy needf reconstruction. We concluded that the tourism in Pirenópolis is representative of a historic and cultural legacy, whereas in Goiânia the metropolis tourism takes place with the same dynamics as the city, in a frantic way, without giving room to contemplations, meeting the needs of another tourist segment. In sum, the present research does not aim at exhausting the subject; on the contrary, we believe that the study of hosting means reflecting on one of the physiological needs that are innate in human beings.